2023
DOI: 10.1155/2023/7412714
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Zinc Oxide Nanoparticles via Leaf Extracts of Catharanthus roseus (L.) G. Don and Their Application in Improving Seed Germination Potential and Seedling Vigor of Eleusine coracana (L.) Gaertn

Abstract: The ecofriendly nature of materials used in synthesis and their low cost make biosynthesized nanoparticles excellent stuff for a broad range of applications in bioscience. Green nanomaterials are progressively used in agriculture to deliver plant nutrients efficiently and effectively. The present work aimed to biosynthesize zinc oxide nanoparticles (ZnO NPs) utilizing Catharanthus roseus (L.) G. Don leaf extracts to use them as a nanopriming agent for improving seed germination and seedling growth in Eleusine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
(61 reference statements)
2
6
0
Order By: Relevance
“…26 Recent studies have shown that ZnO-NPs can be used for treating crops, thus improving seed germination, plant vigor index, physiological and biochemical traits, and biomass production. 42,46,47 In addition, the biogenic ZnO-NPs obtained from duckweed (the same used in the present study) revealed a beneficial effect in maize and olive tree explants. 21,29 As for maize, the biogenic ZnO-NPs positively influenced the chlorophyll and carotenoid content and the cellular redox state, and stimulated biomass production.…”
Section: Discussionsupporting
confidence: 52%
“…26 Recent studies have shown that ZnO-NPs can be used for treating crops, thus improving seed germination, plant vigor index, physiological and biochemical traits, and biomass production. 42,46,47 In addition, the biogenic ZnO-NPs obtained from duckweed (the same used in the present study) revealed a beneficial effect in maize and olive tree explants. 21,29 As for maize, the biogenic ZnO-NPs positively influenced the chlorophyll and carotenoid content and the cellular redox state, and stimulated biomass production.…”
Section: Discussionsupporting
confidence: 52%
“…Additionally, Subbaiah et al 38 showed how raw-ZnO-NPs (mean size was 25 nm) improved the percentage of germination in maize seeds at 1500 mg L −1 . The germinating percentage of finger millet seeds significantly increased at ZnO-NP concentrations of 100 and 500 mg L −1 compared to control, while it decreased at 1000 mg L −1 concentration, according to Mishra et al, 39 who synthesized ZnO-NPs using Catharanthus roseus (L.) leaf extract. After taking everything into account, it was shown that ZnO-NPs, regardless of their concentration, color, traditional method of synthesis or form, have no adverse impact on the germination of wheat seeds.…”
Section: Resultsmentioning
confidence: 91%
“…A healthy seed germination and early seedling stage are important for plants, helping to tolerate stress factors successfully, and significantly affecting the growth of plants. 39 It is crucial to measure the root (radicle) and shoot (plumule) elongation in addition to germination percentage when analyzing the positive or negative impacts of produced ZnO-NPs on the seedling stage of wheat. For this reason, the measurements of length of roots and shoots were realized in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations